Exploring Concepts, Motives and Psychosocial Correlates of Alter Accounts in Indonesia: Menggali Konsep, Motif dan Korelasi Psikososial dari Akun Alter di Indonesia - Nugroho, Irfan Helmi (Psikologia : Jurnal Psikologi, 2025)
The rapid development of social media technology allows individuals to present themselves and interact freely. Some people are known to create new identities on social media that differ from their real-life identity, known as alter accounts or “akun alter” in Indonesian. The phenomenon of alter accounts on Indonesian social media is relatively new. Although several studies have been conducted, there has been no review of the existing literature. This narrative review aims to explore in depth the concepts, motives, and psychosocial factors related to the phenomenon of alter accounts on Indonesian social media. A literature search was conducted in the Google Scholar database with keywords related to “alter accounts” and “social media”. In accordance with the inclusion criteria, titles and abstracts obtained from the search were examined and irrelevant articles discarded. A total of 2,380 research articles were found in the initial search, and 30 unique articles were included in the review. This narrative review defines the concept of alter accounts, which had previously not been clearly defined, and examines the motives behind the use of alter accounts. This review also demonstrates how alter accounts, as digital identities, are connected to an individual’s psychosocial factors. Highlights: Definition and Novelty: Alter accounts are distinct digital identities on social media, and this review offers one of the first clear definitions in the Indonesian context. Motives for Use: Users create alter accounts for reasons such as anonymity, self-expression, and escaping real-life social pressures. Psychosocial Connection: The use of alter accounts is closely linked to individual psychosocial factors, including identity exploration and emotional coping. Keywords: Alter Accounts, Social Media, Psychosocial, Digital Identity